(untitled) (Research, Society and Development, 2021)
Hematopoietic Stem Cell Transplantation (HSCT) is used as standard treatment for a variety of hematologic malignancies. Patients undergo intensive myeloablative treatment before receiving a transplant, putting them at risk of developing serious complications. Oral mucositis, xerostomia and fungal infections, the most common after HSCT. Thus, an integrative literature review was conducted with the aim of evaluating possible oral toxicities in post-HSCT patients, their risk factors, symptoms and manifestations, seeking to identify a correlation between bone marrow transplantation and the development of oral changes. The study consists of a basic bibliographic review, descriptive-explanatory, with integrative and qualitative analysis. A search was performed based on search platforms searching for the terms, “hematopoietic stem cell transplant”, “oral toxicities” and “oral changes”. Articles in English and Portuguese were included, publication in 15 final articles. There are several oral toxicities resulting from immunosuppression and antineoplastic treatment using stem cells; which decrease the survival of patients and their quality of life, in addition to being associated with an increase in systemic infections, costs and hospitalization days. Therefore, it is extremely important that dentists master this subject, and know how to intervene correctly, not only to provide comfort to the patient, but also to avoid and/or reduce systemic complications arising from the oral cavity.